‘Direct Training’ Practical Learning Model on the Teaching Material Diesel Fuel Injection System - Iman Taka, Buyung; Qudus, Nur; Anis, Samsudin (Journal of Vocational and Career Education, 2019)
This research and development study developed a direct training of practical learning model on the teaching material diesel fuel injection system. It aims to determine the validity, practicity and effectiveness of the practical learning model on the teaching material diesel fuel injection system. The study employed research and development (R & D) method with before after without pretest and posttest control design. This study adopted three stages: planning, implementation, and evaluation. The results showed that the direct training of practical learning model was valid. The validity was shown by the average score of the 1st expert on the second cycle of 3.77 and the 2nd expert on the second cycle of 3.46 with a highly valid category and highly feasible to use. The results of the practicity questionnaire given to 20 students and 2 teachers shown as very practice with the final score 86.60. In addition, the assessment of learning effectiveness was performed using T- Test with a significance level of 95%. The result of paired samples T – Test showed the probability value = 0,000 < 0,05 and the average value of gain test = 0, 67 indicating an increase in the medium category. It can be concluded that the direct training of practical learning model was proven able to improve the students skills on diesel fuel injection system.